Autonomic innervation of the cardio-vascular system in normal tension glaucoma patients - N. I. Kurysheva; V. N. Trubilin; M. A. Tsaregorodtseva; T. Ya. Ryabova; V. N. Shlapak; E. Yu. Irtegova (Oftalʹmologiâ)
Purpose: to determine whether there is any difference in autonomic innervation of the cardio-vascular system in normal tension glaucoma (NtG) patients and primary open angle glaucoma (POAG) patients.Methods: 30 NtG patients, 30 POAG patients and 22 control group patients underwent photoplethysmography following cold provocation testing. Several parameters showing cardio-vascular innervation have been evaluated and compared in three groups.Results: the three selected parameters demonstrated the dominance of the sympathetic nervous system over parasympathetic nervous system in both glaucoma groups (NtG and POAG) and not in the control group. In contrast to POAG and the control group, the NtG patients showed strong increase in sympathetic nervous system activity following the cold provocation test.Conclusion: Our studies revealed the dominance of sympathetic innervation in glaucoma patients in general. the cold provocationtest results strongly suggest primary vascular dysregulation in NtG patients.